ALMARFŪ‘ᾹT DALAM SURAT YĀSĪN DAN MODEL PEMBELAJARAN QAWᾹ‘ID-NYA UNTUK PEMULA - Mufhimah, Ziha Fikri; Sunarko, Asep; Al-Khasy, Moh. Ali Qorror; Farandika, Azzahra Rabi; Fahmi , Dalla Sahal; Sindo, Pablo (DAS Institute, 2023)
This research aims to 1) find out the variety of almarfūʻāt in Surah Yasin, 2) find out the qawāʻid almarfūʻāt learning model for beginners, and 3) understand the concept of almarfūʻāt learning for beginners. This research uses qualitative research in the form of literature. Using primary data sources, namely the Al-Quran Al-Karim, the book Matn Jurumiyah by Ahmad Zaini Dahlan, and the book Iʻrobul Koran bil Qiraati Asyrah Almutawatir. And secondary data in the form of books that are relevant to the research focus. So the data collection technique uses documentary study techniques and online data search techniques. Then, analyze the data using content analysis and discourse analysis. The results of the research show that there are 234 isim-isim that are read by rofaʻ in Surah Yāsīn with details of 96 fāʻil consisting of 8 isim ẓāhir and 88 isim ḍamir (35 ḍamir mustatir and 53 ḍamir bariz), 9 nāibul fāʻil consisting of 2 isim ẓāhir and 7 isim ḍamir, 38 mubtadaʻ consisting of 18 mubtadaʻ isim ẓāhir (10 mubtadaʻ isim ẓāhir muqoddam, and 8 muakhar) and 21 mubtadaʻ isim ḍamir , 47 khabar consisting of 16 khabar mufrod and 31 khabar ghoiru mufrod, 11 isim kana, 19 khabar inna. And 14 tābiʻ consisting of 11 naʻat, 2 aṭaf, and 1 badal. The learning model uses RPP (learning implementation plan) with fa'il and mubtada' khabar material as an example. The concept of al-marfūʻāt learning takes the theme of أَلْأَدَاوَتُ الْمَدْرَسيَّةِ (school equipment), several examples of al-marfūʻāt in Surah Yāsīn to be used as examples, learning materials, practices and exercises for students. To understand the contents that rofaʻ reads in learning Arabic. Learning Arabic material on al-marfūʻāt MTs class VII uses a structural approach. The learning method uses inductive and deductive methods. The techniques used are in accordance with the 4 Arabic language skills, namely listening, speaking, reading and writing. The learning media used consists of the teacher's voice, whiteboard, reading text and pictures. Learning evaluation consists of non-test techniques in the form of observation, as well as test techniques in the form of formative tests.